The "Cutaneous Rabbit" Hopping out of the Body - Miyazaki, Makoto; Hirashima, Masaya; Nozaki, Daichi (The Journal of neuroscience, 2010)
Rapid sequential taps delivered first to one location and then to another on the skin create the somatosensory illusion that the tapping is occurring at intermediate locations between the actual stimulus sites, as if a small rabbit were hopping along the skin from the first site to the second (called the “cutaneous rabbit”). Previous behavioral studies have attributed this illusion to the early unimodal somatosensory body map. A functional magnetic resonance imaging study recently confirmed the association of the illusion with somatotopic activity in the primary somatosensory cortex. Thus, the cutaneous rabbit illusion has been confined to one's own body. In the present paper, however, we show that the cutaneous rabbit can “hop out of the body” onto an external object held by the subject. We delivered rapid sequential taps to the left and right index fingers. When the subjects held a stick such that it was laid across the tips of their index fingers and received the taps via the stick, they reported sensing the illusory taps in the space between the actual stimulus locations (i.e., along the stick). This suggests that the cutaneous rabbit effect involves not only the intrinsic somatotopic representation but also the representation of the extended body schema that results from body–object interactions.